Nove noites: o discurso do narrador e a construção do personagem na ficção contemporânea - Bergamim, Claudia Regina (2006)
We emphasize the narrator s work in the storytelling to show how contemporary fiction uses the aesthetic resource in its representation. For that end, we intend to investigate the effect of having two narrators in the novel Nove noites, by Bernardo Carvalho, published by Companhia Das Letras, in 2002. From the report of each narrator we will observe the marks that characterize their speeches in order to define the role of this fictional component. We will also consider the changes that have taken the aesthetic components to alternative positions inside the story, as a way to cunningly place in the art of telling stories. We also hope to show how this modern-day-narrator s speech can produce a text that mixes real and imaginary friends and not break up its commitment to fiction. Bernardo Carvalho presents himself as a writer who is conscious of the literary work and his work elevates lose the reader as he follows the text, or maybe this is just a way to disguise the absence of a meaning. In that aspect, the narrator is the component who shows a proposal of a story with such characteristics once he is a fictional space, in a position that is very different from that of the experienced storyteller who used to add his wisdom to the text. From an angle that allows us to identify him with the reader, for he also takes the position of a reader, the narrator highlights the importance of the character and subtracts himself from the story he told. However, his imagination and creativity do not let us fail to see his presence in the story